Learning in the Experiential Continuum: A Philosophically Informed View of Professional Socialisation - Faúndez-Aedo, Matías (Nursing philosophy, 2026)
Professional socialisation is a concept that encapsulates the multifactorial and complex learning process through which a person becomes a member of a profession. In the field of nursing, existing literature on professional socialisation has primarily focused on describing students' key learning experiences during university education. This tendency has been crucial to identifying and characterising the relevance of students' interactions with faculty, patients, and peers and their engagement with the occupational culture and institutional norms, among other learning experiences. However, few studies have taken a step back to elaborate on the theoretical underpinnings of students' socialisation, such as the underlying approach to learning or, more fundamentally, what is understood by human experience. We argue that this omission has precluded a more comprehensive view of professional socialisation. Addressing this gap, in this article, we integrate philosophy to develop a framework that intertwines the concepts of experience, learning, and socialisation. In so doing, we propose that learning occurs within an experiential continuum. Ultimately, this framework operates as theoretical scaffolding that offers a deeper understanding of students' learning during professional socialisation and paves the way for new avenues of empirical research.